Point of Care Ultrasonography to Assess the Pulmonary Fluid Status for The Septic Patient Requiring Fluid Resuscitation in The Emergency Department - Mirza, Rida Tariq; Mustafa, Khawaja Junaid; Radiyah, Eisha Tir; Mirza, Mahrukh (Biological and Clinical Sciences Research Journal, 2025)
Sepsis is a major cause of morbidity and mortality worldwide, requiring timely fluid resuscitation to restore perfusion. However, indiscriminate fluid administration may lead to pulmonary congestion and worsen outcomes. Point-of-care ultrasonography offers a rapid, non-invasive method to assess pulmonary fluid status and guide individualized fluid therapy in septic patients. Objective: To evaluate the effectiveness of point-of-care ultrasonography in assessing pulmonary fluid status and predicting fluid responsiveness among septic patients requiring initial fluid resuscitation in the emergency department. Methods: A prospective observational study was conducted from April to September 2024 in the emergency department of a tertiary care hospital. Ninety adult patients with sepsis or septic shock requiring fluid resuscitation were enrolled. Lung ultrasound and inferior vena cava (IVC) collapsibility index were assessed before and after initial fluid boluses. B lines were quantified using a standardized multizone protocol. Fluid responsiveness was evaluated using changes in mean arterial pressure and clinical perfusion markers. Statistical analysis included chi-square and independent t-tests, with significance set at p ≤ 0.05. Results: The mean age was 51.6 ± 15.2 years, with 60 percent male patients. Baseline B lines were present in 32.2 percent of patients, increasing to 45.6 percent after fluid administration, indicating evolving pulmonary congestion. Patients with IVC collapsibility greater than 50 percent showed significantly higher rates of fluid responsiveness (63.3 percent vs 26.7 percent, p = 0.002) and a lower incidence of new B lines. Absence of baseline B lines was associated with better hemodynamic response (58.3 percent vs 31.1 percent, p = 0.01). Ultrasound-guided assessment enabled identification of patients at risk of fluid overload and reduced the need for ventilatory escalation. Conclusion: Point-of-care ultrasonography is a reliable bedside tool for guiding early fluid resuscitation in sepsis. Combined assessment of lung B lines and IVC collapsibility improves identification of fluid-responsive patients and reduces pulmonary congestion, supporting safer, individualized fluid strategies in emergency settings.